Fabricating method of SU-8 photoresist conical nozzle for inkjet printhead. Issue 8 (11th June 2018) - Yi, Maocong; Feng, Jianbo; Yin, Zhifu; Zou, Helin
ABSTRACT: A novel conical nozzle fabrication method for piezoelectric inkjet printhead is proposed based on the microelectromechanical system technology. By optimizing the exposure gap, exposure dose, postexposure bake (PEB), and development time, the SU-8 conical nozzle was fabricated. After thermal bonding with an open chamber, the piezoelectric inkjet printhead chamber was formed. The results show that the optimum SU-8 conical nozzle can be fabricated by applying exposure dose of 105 mJ/cm 2, exposure gap of 50 µm, PEB temperature of 65°C, PEB time of 10 min, and development time of 210 s. The final size of optimum conical nozzle is the large aperture of 30.46 ± 1.17 µm, small aperture of 20.34 ± 1.42 µm, and nozzle height of 45.38 ± 1.02 µm.